Assessing cognition and function in Alzheimer's disease clinical trials: Do we have the right tools?. Issue 6 (1st November 2014) - Snyder, Peter J.; Kahle‐Wrobleski, Kristin; Brannan, Stephen; Miller, David S.; Schindler, Rachel J.; DeSanti, Susan; Ryan, J. Michael; Morrison, Glenn; Grundman, Michael; Chandler, Julie; Caselli, Richard J.; Isaac, Maria; et al.
Abstract: Several lines of evidence from Alzheimer's disease (AD) research continue to support the notion that the biological changes associated with AD are occurring possibly several decades before an individual will experience the cognitive and functional changes associated with the disease. The National Institute on Aging—Alzheimer's Association revised criteria for AD provided a framework for this new thinking. As a result of this growing understanding, several research efforts have launched or will be launching large secondary prevention trials in AD. These and other efforts have clearly demonstrated a need for better measures of cognitive and functional change in people with the earliest changes associated with AD. Recent draft guidance from the US Food and Drug Administration further elevated the importance of cognitive and functional assessments in early stage clinical trials by proposing that even in the pre‐symptomatic stages of the disease, approval will be contingent on demonstrating clinical meaningfulness. The Alzheimer's Association's Research Roundtable addressed these issues at its fall meeting October 28–29, 2013, in Washington, D.C. The focus of the discussion included the need for improved cognitive and functional outcome measures for clinical of participants with preclinical AD and those diagnosed with Mild Cognitive Impairment due to AD.